PENGARUH WORD OF MOUTH DAN BRAND LOYALTY TERHADAP PURCHASE INTENTION AIR MINERAL DALAM KEMASAN UTRA PADA PT GUWATIRTASEJAHTERA - Erwan Nurhidayat; Hidup Marsudi (Akademi Pelayaran Nasional Surakarta, 2020)
In the era of rapid development of nearly everyone consume bottled mineral water. This affects the mineral water company is developing rapidly. One of them is AMDK company (AIR MINUM DALAM KEMASAN) Guwatirta Sejahtera Company with name brand Utra. Therefore Utra must be excelent improve continue and innovate to attract attention and get his confidence of consumers in order to create a consumer buying interest that continues to exist in the market.This purpose of this research is determine the effect of word of mouth and Brand Loyalty to Purchase Intention sample that amount taken from 77 respondents. Measurement variables using research instruments such as questionnaires. The Methods of data analysis is a method of Validity, reliability testing, t Test, F test and R2 test.The results of the test is indicate that Word of mouth and brand loyalty positve and significant effect on purchase intention. Increased purchase intent for the review should be through influential because big brand loyalty , brand loyalty singer must be supported and enhanced by the company.